Evaluation of Citation Inaccuracies in Surgical Literature by Journal Type, Study Design, and Level of Evidence: Towards Safeguarding the Peer-Review Process. Issue 7 (July 2022) - Sauder, Matthew; Newsome, Kevin; Zagales, Israel; Autrey, Cody; Das, Snigdha; Ang, Darwin; Elkbuli, Adel
Background: Accurate citation practices are key to furthering knowledge in an efficient and valid manner. The aim of this study is to investigate the prevalence of citation inaccuracies in original research from the top-ranked surgical journals and to evaluate the impact level of evidence has on citation inaccuracy. Methods: A retrospective study evaluating the citation accuracy of the top 10 ranked surgical journals using the SJCR indicators. For each year between 2015 and 2020, the top 10 cited studies were selected, totaling 60 studies from each journal. From each individual study, 10 citations were randomly selected and evaluated for accuracy. Categories of inaccuracy included fact not found, study not found, contradictory conclusion, citation of a citation, and inaccurate population. Results: A total of 5973 citations were evaluated for accuracy. Of all the citations analyzed, 15.2% of them had an inaccuracy. There was no statistically significant difference in citations inaccuracy rates among the years studied ( P = .38) or study level of evidence ( P = .21). Annals of Surgery, Plastic and Reconstructive Surgery and Annals of Surgical Oncology had significantly more citation inaccuracies than other journals evaluated ( P < .05). JAMA Surgery, The Journal of Endovascular Therapy and The Journal of Thoracic and Cardiovascular Surgery had significantly fewer citation inaccuracies. Conclusions: Although 84.8% of citations from 2015-2020 were determined to be accurate, citation inaccuracies continue to be prevalent throughout highly-ranked surgical literature. There were no significant differences identified in citation inaccuracy rates between the years evaluated or based on study level of evidence.